Neoclassical and Behavioural Asset Pricing Models : The Case of Sri Lanka - Perera, Shenali Anne (2013)
This study aims to provide a better understanding of the Sri Lankan stock market in terms of asset pricing models. In order to achieve this goal this research evaluates the Fama and French three-factor model and a behavioural asset pricing model to investigate which framework is better suited for security valuation in Sri Lanka. Accordingly findings reveal that small stocks with low book-to-market equity generate high realized returns. But results indicate that superior returns on these stocks are more likely due to investor irrationality rather than as a compensation for higher risk. Hence it was concluded that a behavioural asset pricing model is more suitable in the context of Sri Lanka. Additionally this study also finds that behavioural heuristics such as representativeness lead investors to incorrectly believe that stocks of reputed companies will generate high returns. The findings of this study will be invaluable for policy-makers to enhance the efficiency of the Colombo Stock Exchange and contribute towards economic growth. Furthermore this research allows improved investor decision-making by highlighting profitable investment strategies and also by enhancing awareness of cognitive errors and behavioural biases that cause investors to make inaccurate decisions.